Perbuatan Melawan Hukum Oleh Notaris dalam Pembuatan Akta Rapat Umum Pemegang Saham Perseroan Terbatas (Studi Putusan Nomor 10/Pdt.G.S/2023/Pn.Pdg) - Salma, Ta'tiana (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study examines the unlawful act committed by a notary in making the deed of the general meeting of shareholders. This study aims to analyze how the judge's legal considerations in qualifying the Notary's actions as the making of the Deed of the General Meeting of Shareholders as an Unlawful Act and how the Judge's legal considerations in granting a claim for compensation for the Unlawful Act of the Notary in making the Deed of the General Meeting of Shareholders in Decision No. 10/Pdt.G.S/2023/PN.Pdg. This research uses a normative juridical research type, a statutory approach method. With the specification of analytical descriptive research associated with theory. The data used is secondary data which is used by collecting data using library research which is presented through systematic and logical descriptions in the form of narrative text, then analyzed in a qualitative normative manner. Based on the results of research and data analysis, the Notary has committed an Unlawful Act in accordance with Article 1365 of the Civil Code in making the Deed of the General Meeting of Shareholders which was not based on a separate Deed of Grant by the Plaintiff, because his actions resulted in the Plaintiff losing his position as a Shareholder and is obliged to compensate for losses, namely restoration of circumstances or Restitutio In Integrum as Shareholders and Directors at PT. Intercom Mobilindo.